Study on the New Method of Constructing Shear Walls in Multi-Storey Buildings With Site Cast Reinforced Concrete Frame System - Lusine Gurgen Karapetyan; Tigran Vardan Ter-Poghosyan (Journal of Architectural and Engineering Research, 2021)
The article touches upon the comparative analysis of bearing system calculations of a multi-storey residential building with site cast reinforced concrete frame and shear wall constructed by two different methods.  In the calculation models, the shear walls are constructed from site cast reinforced concrete in the first case, and from three-layer sound and thermal insulating bearing panels in the second. The calculations have been made considering the impact of the seismic force. According to the calculation results, the dynamic parameters of the bearing systems of the buildings and the economic efficiency indicators have been compared. Considering the fact that in the recent years three-layer sound and thermal insulating panels have been widely used in the world, the study attempted to reveal the efficiency of using such panels in the Republic of Armenia.